Performance improvements and increased ruminal microbial interactions in Angus heifers via supplementation with native rumen bacteria during high-grain challenge - Fan Yang; Madison T. Henniger; Andrew S. Izzo; Emily A. Melchior; Brooke A. Clemmons; Mary A. Oliver; James R. Gaffney; Cameron Martino; Taylor B. Ault-Seay; Miranda L. Striluk; Jordan J. Embree; Juan F. Cordero-Llarena; et al. (Scientific Reports)
Abstract Feedlot cattle may be subjected to digestive disorders, including ruminal acidosis, due to high concentration of grain in their diet. Therefore, novel feeding strategies are required to maximize animal performance and mitigate economic losses in the operation. This study employed a two-period crossover design to assess the effect of direct ruminal administration of native rumen microorganisms (NRM) inoculation on cattle that underwent a high-grain challenge. The NRM inoculation consisted of six microorganisms (1.70 M CFU /day/animal) isolated from the rumen of healthy feedlot cattle: Succinivibrio dextrinosolvens ASCUSBF53, Prevotella albensis ASCUSBF41, Chordicoccus furentiruminis ASCUSBF65, Bacteroides xylanisolvens ASCUSBF52, Clostridium beijerinckii ASCUSBF26, and Syntrophococcus sp. ASCUSBF60. The trial consisted of 16 Angus heifers receiving NRM (n = 8) or a CON (CON = Carrier Buffer; n = 8) inoculation daily for 14-days as pre-challenge while on a high-grain diet and continued daily for a 21-day treatment period. The combined 35 days of microbial supplementation resulted in an improved average daily gain (ADG) of 29% (P = 0.037) and a tendency toward a 19% decrease in the feed efficiency metric, gain to feed ratio (G: F) (P = 0.055). Additionally, administration of NRM to animals on a high-grain diet, improved ruminal microbiome stability (P < 0.001), potentially encouraging the conversion of rumen lactate to propionate over time via the succinate pathway and alleviating metabolic stress.